KUALITAS KIMIA ESSENTIAL OIL DARI KULIT JERUK PURUT HASIL HYDRODISTILLATION KELOMPOK MASYARAKAT DI BADUNG BALI - Gusti Ayu Dewi Lestari (Randang Tana - Jurnal Pengabdian Masyarakat, 2024)
Kaffir lime (Citrus hystrix DC.) is an economical product and has high health value. Generally, kaffir lime peel is the part that contains a lot of essential oils, so it is used by community groups in Badung Regency, Bali, specifically in Dalung Village, to extract this essential oil. The aim of this activity is of course to chemically test the quality of the products that partners have produced which will then provide knowledge to partners about the importance of producing good quality so that the products produced are able to compete in society. A GC-MC (Gas Chromatography-Mass Spectroscopy) test was carried out on this essential oil to determine the content of the essential oil that has been produced by the partner, where the GC-MS results showed that the essential oil of kaffir lime skin produced by the partner was 81,90% citronella compounds. In this service activity, community understanding regarding essential oils was also carried out, where with this activity, community understanding increased as seen from the pre-test and post-test scores.